PENGEMBANGAN MEDIA DAKON EDUKATIF BERBASIS PROFIL PELAJAR PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI IDE POKOK PARAGRAF SISWA KELAS V SDN KEMLOKO 01 KECAMATAN NGLEGOK - Triani, Heppy Novi; Alfi, Cindya; Fatih, Mohamad (STKIP Persada Khatulistiwa Sintang, 2024)
The study aims to produce educational dakon learning media products based on Pancasila student profiles to improve learning outcomes on the main idea paragraph material for grade V SDN Kemloko 1 Nglegok District which are valid based on material experts and media experts, and are suitable to be used by teachers and students who can improve the learning outcomes of grade V students. This study uses the ADDIE development model. The results of the validity test of the educational dakon product show a level of validity that is very valid and valid with a validation score percentage of 91%, 80% and 80%. The results of the feasibility test of the educational dakon product are very feasible with a percentage of 91.11%. The results of the pretest and posttest of students on the educational dakon product show that the educational dakon media can improve student learning outcomes with the N-gain score obtained reaching 0.45 with a moderate category. Thus, the educational dakon product produced is valid and suitable to be used in learning the main idea paragraph material at grade V.